PERBANDINGAN EFEKTIFITAS INOKULUM CAIRAN RUMEN KERBAU DAN SAPI PADA JERAMI - Hifizah, Amriana (Teknosains, 2013)
Bacteria type pendegradasi fibers have often in isolation from liquid rumen good bovine cattle, the buffalo, goat or a horse, henceforward bred and becomes inokulum to ferment feed derived from an agricultural waste / estates basically having fibers which was high and levels of a protein low. So inokulum containing microbes selulolitik already isolated from liquid rumen was expected to lower levels coarse fiber from feed of hay and on the other increase levels of a protein feed origin the waste. This writing tmean review some literature research with the intent of comparing effectiveness inokulum asal a liquid rumen cattle and the buffalo as fermentor on feed asal an agricultural waste for example, straw. Inokulum asal a liquid rumen buffalo is the best in degrades feed fiber derived from an agricultural waste. This is because of the buffalo able to benefit from feed with the quality of low because supported by volume rumen water buffaloes do large, the secretion of saliva tinggi, the rate of feed leave rumen slow as well as activity selulolitik and populations of microbes that are higher. The granting of a liquid rumen as many as 50 - 200ml / 1 ltr solution as bio inokulan can improve nutritional value of fodder, meanwhile, if used inokulum bacteria selulolitik from a liquid rumen can be used as much as 10-15 % in rations straw.Key words: Inokulum, Bacteria Selulolitik, A Liquid Rumen, Straw